Fluvial hydrology and geomorphology of Monsoon-dominated Indian rivers - Vishwas S. Kale (Revista Brasileira de Geomorfologia, 2005)
The Indian rivers are dominantly monsoon rainfed. As a result, their regime characteristics are dictated by the spatio-temporal variations in the monsoon rainfall. Although the rivers carry out most of the geomorphic work during 4-5 months of the monsoon season, the nature and magnitude of response to variations in the discharge and sediment load varies with the basin size and relief characteristics. Large monsoon floods play a role of great importance on all the rivers. This paper describes the hydrological and geomorphological characteristics of the two major fluvial systems of the Indian region, namely the Himalayan fluvial system and the Peninsular fluvial system. Large number of studies published so far indicate that there are noteworthy differences between the two river systems, with respect to river hydrology, channel morphology, sediment load and behaviour. The nature of alterations in the fluvial system due to increased human interference is also briefly mentioned. This short review demonstrates that there is immense variety of rivers in India. This makes India one of the best places to study rivers and their forms and processes.